An empirical investigation of purchasing power parity for a transition economy - Cambodia - Liew, Venus Khim-Sen; Tuck , Cheong Tang (Monash University Bussiness anf Economics, 2009)
This study has found an empirical support of Purchasing Power Parity (PPP) theory for an East Asia transition economy – Cambodia. It is based on the results of cointegration among KHR/USD, Cambodia CPI, and world CPI over the monthly period May 2001-February 2009. This finding is useful for policy implications i.e. de-dollarization (and exchange rates) policy designs in Cambodia.